PENGARUH KUALITAS PELAYANAN TERHADAP WORD OF MOUTH, MELALUI KEPERCAYAAN DAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA STAR CLEAN CAR WASH SEMARANG - Taufiq Dwi Satmoko; Handoyo Djoko Waluyo; Ngatno Ngatno (Universitas Diponegoro, 2016)
This modern age, many people are busy with their lives. They are willing to work to night so not had of looking at other things such as vehicles. Community activities that tend to be practical so that it becomes an opportunity for service providers to offer their services car wash to wash the vehicle. One company car wash in Semarang, namely Star Clean car wash is one company that is growing, but the number customer experience fluctuations during the year 2010-2013 along with some of the targets were not achieved targets.This study aims to determine the effect on the quality of their service through word of mouth and customer satisfaction Star confidence Clean car wash Semarang. This type of research is explanatory. The population in this study is the Star Clean car wash customers in Semarang, using the theory Slovin then taken 100 respondents to be sampled and the sampling technique used was purposive sampling. Methods of data collection using questionnaires, interviews and literature method. Measurement scale using a Likert scale. In the data analysis using validity, reliability test, correlation coefficient, analysis of simple and multiple linear regression, the coefficient of determination, significance test (t test and F) and Sobel test with SPSS.The study concluded that the quality of service, reliability and customer satisfaction together (simultaneously) or partially affect the variable word of mouth. Based on the test results Sobel, a direct influence on the quality of service word of mouth is greater than its indirect influence through a trust or through customer satisfaction.Suggestions in this research that Star Clean car wash Semarang should increase speed and always menontrol network of free hotspots and to boost consumer confidence should always control the work performed by the employee. As well as consumer satisfied that leaders should try to improve the ability of employees in ethical.